Effect of Organic Farming on Nutrient Uptake and Quality of Potato (Journal of Environmental Science and Natural Resources, 2013)
The experiment was carried out at the Environmental Science Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period November 2004 to February 2005 to evaluate the effect of organic farming on soil and potato quality. The experiment was laid out in a randomized complete Block Design with five treatment and three replications. The treatments and their combinations were cowdung, poultry manure, inorganic fertilizer, cowdung plus inorganic fertilizer and poultry manure plus inorganic fertilizer. The nutrient content of P, K, Ca, Mg, Zn of tuber and haulm, and starch and protein content in tuber were highest in cowdung treated potato and but N and S content of both tuber and haulm were highest in case of poultry manure. The uptake of P, K, Mg and S of both tuber and haulm in case of poultry manure but N and Zn uptake was highest in case of poultry manure plus inorganic fertilizer. Finally, calcium uptake was highest in cowdung in both cases of tuber and protean and starch contents were influenced by organic farming.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14818 J. Environ. Sci. & Natural Resources, 5(2): 219-224 2012